Development and characterisation of a heparinised fibrin hydrogel as a delivery vehicle for regenerative medicine - Ngcobo, Silindile (Division of General Surgery, 2025)
Fibrinogen is an attractive hydrogel candidate for regenerative medicine due to its inherent biocompatibility, biodegradability, and clinical approval. It is the precursor protein cleaved by the protease thrombin that polymerises into a fibrous network known as fibrin. The present study sought to modify fibrinogen through covalent attachment of heparin to form heparinised fibrin hydrogels. Heparin is known to bind a significant number of growth factors and its anti-coagulative characteristic plays a role in minimising thrombotic events. We therefore developed a novel method for attaching heparin to fibrinogen that allowed for retention of thrombin-based polymerisation. Additionally, the potential of co-modification with polyethylene glycol (PEG) enhancing heparinisation and improving fibrin resistance to proteolytic degradation was assessed. The modified forms of fibrin hydrogel were then assessed for their potential as regenerative hydrogels. To conjugate heparin to fibrinogen, we explored the utility of an acrylated form of heparin (developed in Professor Bezuidenhout's Polymer Laboratory) that preferentially binds to thiol groups (such as cysteine side chains in proteins) via a Michael-type addition reaction. As additional free thiols might increase heparin binding, we also modified the fibrinogen with a n-hydroxysuccinimide-PEG-thiol (NHSPEG-SH) molecule, and a maleimide based assay confirmed that 0.75 free thiols were successfully bound to fibrinogen to form modified fibrinogen-PEG-SH (FP). This represented a greater than 100-fold increase in free thiols present in native fibrinogen. This binding was further confirmed with a Fourier-transform infrared spectroscopy. Fibrinogen and FP were then assessed for hep-acr binding. Two assays were used for heparin quantification, namely calorimetric 3-Methyl-2- Benzothiazolinone Hydrazone assay modified for quantification of protein bound heparin, and a commercial fluorescent probe-based assay. Both assays showed that hep-acr was successfully conjugated to fibrinogen and FP at 0.2-0.3 molecules of heparin bound per either molecule to form fibrin(ogen)-heparin (FH) and fibrin(ogen)- peg-heparin (FPH) respectively. Binding through the acrylate moiety was confirmed with non-acr hep binding at 10 times lower levels. All modified forms of fibrinogen retained the ability to polymerise via the action of thrombin. Though not amplifying heparinisation, PEGylation and heparinisation combined strongly protected fibrin from spontaneous in-vitro degradation at 37ºC compared to all other hydrogel formulations (fibrin and FH were 100% degraded by day 5; FP by day 6 and FPH only by 57% at day 15). Micrographs from scanning electron microscopy (SEM) revealed a more fibrillar structure after polymerisation for FH closer in morphology to that of fibrin, while FP and FPH both formed more sheet like structures. Rheology showed a reduction in storage modulus/ mechanical stiffness for FP (18.3 ± 1.3 Pa) and FPH (17.6 ± 2.7 Pa) compared to normal fibrin (42.1 ± 1.5 Pa) and FH (36.7 ± 1.9 Pa). Despite these differences, both FH and FPH were antithrombotic as determined by the attached heparin completely impeding clot formation for the duration of analysis (2 hours) with thromboelastography, as compared to whole blood, fibrinogen, and FP which formed clots within 1.4 ± 0.1, 1.5, and 1.3 ± 0.1 min respectively. All the hydrogels were biocompatible, with viability percentages not less than 70% after three days of 3D culture for all three cell lines evaluated, namely human umbilical vein endothelial cells (HUVECs), human dermal fibroblasts and adipose tissue-derived stem cells (ADSCs) as indicated by live/dead assays. A 3D HUVEC spheroid-based angiogenesis assay found that FH substantially stimulated formation of capillary-like structures relative to fibrin. When evaluated for growth factor release in-vitro, the burst release in the first day was reduced by 5-fold for both basic fibroblast growth factor (bFGF) and vascular endothelial growth factor (VEGF) in the presence of heparin. Both FH and FPH further prolonged and sustained bFGF and VEGF release in-vitro relative to their unheparinised counterparts. The FH and FPH released 16 ± 0.7 and 16 ± 0.7 ng bFGF per day, and 20.5 ± 2.2 ng and 18.4 ±1.6 ng VEGF per day up to 15 days respectively with bioactivity maintained. An initial in-vivo subcutaneous rat model study of fibrin formulations loaded with 1 µg of VEGF showed pronounced vessel formation into all forms of fibrin independent of VEGF after 10 days. A significant increase in vessel ingrowth for either heparinised form of fibrin was not observed. This dosage of VEGF has previously been seen to stimulate neovascularisation into heparinised PEG hydrogels in our laboratory and it was hypothesised that the high levels of vascularisation stimulated by fibrin alone may have obscured the VEGF induced angiogenesis. Further studies exploring VEGF dosage and concentration of fibrin hydrogels should be carried out. As delivery of stem cells within hydrogels is a key present function of regenerative hydrogels, the impact of the heparinised fibrinogens on ADSC differentiation underwent preliminary investigation. The impact of heparin on mesenchymal stem cell differentiation is presently unclear with several contradictory reports in the literature. Predictably the soft fibrin hydrogels in all formulations strongly promoted adipogenesis relative to stiff tissue culture plastic (TCP). More surprisingly, osteogenesis was also increased on the fibrin hydrogels relative to TCP. Additionally, heparinisation altered differentiation, where osteogenic differentiation in FH was significantly increased against all groups, while this increase was observed in FH when compared to the FP group for adipogenic differentiation. In conclusion, this study presents two methods of conjugating heparin to fibrinogen to form anti-thrombotic heparinised fibrin hydrogels where polymerisation via thrombin activity was retained. The bound heparin in both hydrogel systems substantially reduced burst release of bFGF and VEGF and allowed for sustained release of bioactive growth factors. The FPH was advantageous in that it reduced inherent fibrin degradation, and provided a transparent physical appearance that was useful in viewing encapsulated cells. The FH did not significantly reduce mechanical stiffness compared to unmodified fibrin, and further encouraged more HUVEC invasion in 3D. All formulations of fibrin hydrogels proved to be significantly better matrices for ADSC adipogenic and osteogenic differentiation as compared to TCP. These findings are crucial for applications in stem cell and, growth factor delivery and ultimately tissue regeneration.